2022
DOI: 10.1186/s12876-022-02570-w
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of noninvasive methods for the diagnosis of liver fibrosis in children with chronic viral hepatitis

Abstract: Background Liver biopsy is the reference standard for assessing liver fibrosis. Moreover, it is an invasive procedure. Transient elastography (TE) is an accurate, noninvasive method for evaluating liver stiffness as a surrogate of liver fibrosis. The aspartate aminotransferase to platelet ratio index (APRI) and Hyaluronic acid (HA) are noninvasive alternatives to liver biopsy for detecting hepatic fibrosis. This study aimed to identify the accuracy of APRI, HA, and TE concerning liver biopsy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…To estimate the accuracy of non-invasive methods for diagnosing liver fibrosis with chronic liver hepatitis, a cross-sectional study was done by [7] for hepatitis B and Hepatitis C patients who underwent liver biopsy within nine months of laboratory tests. They concluded that Transient Elastography was the only method to differentiate mild cases from significant ones.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the accuracy of non-invasive methods for diagnosing liver fibrosis with chronic liver hepatitis, a cross-sectional study was done by [7] for hepatitis B and Hepatitis C patients who underwent liver biopsy within nine months of laboratory tests. They concluded that Transient Elastography was the only method to differentiate mild cases from significant ones.…”
Section: Methodsmentioning
confidence: 99%
“…Currently there is no standard recommendation regarding when to use a FibroScan ® 502, Echosens, Paris, France or transient elastography to assess liver fibrosis in children with HCV infection. However, a FibroScan or transient elastography might be another method to assess liver fibrosis before or after treatment with DAAs [ 29 , 30 ] and to differentiate mild cases from those with significant fibrosis in children with chronic viral hepatitis including HBV and HCV [ 31 ].…”
Section: Further Evaluationmentioning
confidence: 99%
“…This technique has been used to diagnose liver stiffness and fibrosis in the past (15,16). Thus, monitoring the stiffness of the liver over time can show how some liver disorders, including NASH, progress (17). The fundamental idea behind TE is that a homogenous tissue's elasticity, which is connected with the degree of fibrosis in the liver, determines how quickly a wave propagates through it.…”
Section: Introductionmentioning
confidence: 99%